2020
DOI: 10.3390/healthcare8040375
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Transient Effect of Complex and Core Stability Exercises on Static Balance Ability and Muscle Activation during Static Standing in Healthy Male Adults

Abstract: Balance ability is a necessary exercise factor required for the activities of daily living. This study investigated the effects of short-term complex exercise (CE) and core stability exercise (CSE) on balance ability and trunk and lower-extremity muscle activation on healthy male adults. Twenty-nine healthy male adults were included. All performed CE and CSE for 1 min each; the exercise order was randomized. The primary and secondary outcomes were balance ability and muscle activation, respectively. In balance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…In another study, the dynamic balance values of the runners who performed core stabilization exercises were better (18). A research for university students, there is a relationship between the development of core stabilization and static balance (19); In a study conducted by Sekendiz on middle-aged sedentary women, it was stated that there is a relationship between core development and dynamic balance (20). In study with 90-year-old sedentary elderly individuals, found a relationship between core stabilization and strength and dynamic balance (21); It evaluated the relationship between core stabilization and balance of former dancers and sedentary elderly individuals aged 50-87 years and stated that there was a positive relationship (22).…”
Section: Discussionmentioning
confidence: 90%
“…In another study, the dynamic balance values of the runners who performed core stabilization exercises were better (18). A research for university students, there is a relationship between the development of core stabilization and static balance (19); In a study conducted by Sekendiz on middle-aged sedentary women, it was stated that there is a relationship between core development and dynamic balance (20). In study with 90-year-old sedentary elderly individuals, found a relationship between core stabilization and strength and dynamic balance (21); It evaluated the relationship between core stabilization and balance of former dancers and sedentary elderly individuals aged 50-87 years and stated that there was a positive relationship (22).…”
Section: Discussionmentioning
confidence: 90%
“…The study showed that this 4-week sensorimotor training intervention was associated with a significant improvement in static and dynamic balance from baseline in the experimental and placebo groups as compared to the control group. From an efficiency standpoint, in short- and long-term conditions, previous studies found an improvement in postural stabilization and balance parameters as a consequence of 4 weeks of specific sensorimotor training [ 29 , 30 , 31 , 32 ]. The experimental group doing the specific sensorimotor training showed significantly greater improvement in all the postural parameters assessed (postural balance, stability and coordination) as compared with the placebo and control group.…”
Section: Discussionmentioning
confidence: 99%
“…Balance is defined as the ability to maintain the center of mass within a base of support [ 1 , 2 ], and maintenance of balance is considered an essential factor for people to perform functional movements in daily life and recreational activities [ 3 , 4 ]. Functional movements include actions performed in daily life, such as sitting, standing, and gait, and various work or sports-related movements.…”
Section: Introductionmentioning
confidence: 99%